Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/jgm.3333
|View full text |Cite
|
Sign up to set email alerts
|

LINC00460 promotes pancreatic cancer progression by sponging miR‐491‐5p

Abstract: Background: A growing body of studies have suggested that LINC00460 is instrumental in tumorigenesis and tumour progression. Nonetheless, the biological function and mechanisms of LINC00460 in pancreatic ductal adenocarcinoma (PDAC) remain vague.Methods: Analysis based on public databases and a quantitative reverse transcriptionpolymerase chain reaction were performed to screen for differentially expressed lncRNAs in PDAC and to detect LINC00460 expression in PDAC cell lines and clinical samples. The survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…LINC00460 (long intergenic non-protein coding RNA 460) is located on chromosome 13q33.2 and transcribed as a 913-nt transcript. Some studies showed that LINC00460 could promote tumor growth and malignant progression and is correlated with survival in multiple tumor types, including nasopharyngeal carcinoma, papillary thyroid carcinoma, esophageal cancer, gastric cancer, lung cancer, breast cancer, colorectal cancer, renal cell carcinoma, pancreatic cancer, bladder and urothelial carcinoma, ovarian cancer, and meningioma ( Kong et al, 2018 ; Liu W. et al, 2018 ; Liu X. et al, 2018 ; Wang F. et al, 2018 ; Xing et al, 2018 ; Wen et al, 2019 ; Ye et al, 2019 ; Cisneros-Villanueva et al, 2021 ; Hou et al, 2021 ; Qian et al, 2021 ; Wu et al, 2021 ; Yang et al, 2021 ). HNSCC is certainly no exception, with its identification as a prognostic lncRNA signature using orthogonal partial least squares discriminant analysis (OPLS-DA) which integrates RNA-Seq data from TCGA database and matching clinical information from a large cohort of patients with HNSCC( Cao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…LINC00460 (long intergenic non-protein coding RNA 460) is located on chromosome 13q33.2 and transcribed as a 913-nt transcript. Some studies showed that LINC00460 could promote tumor growth and malignant progression and is correlated with survival in multiple tumor types, including nasopharyngeal carcinoma, papillary thyroid carcinoma, esophageal cancer, gastric cancer, lung cancer, breast cancer, colorectal cancer, renal cell carcinoma, pancreatic cancer, bladder and urothelial carcinoma, ovarian cancer, and meningioma ( Kong et al, 2018 ; Liu W. et al, 2018 ; Liu X. et al, 2018 ; Wang F. et al, 2018 ; Xing et al, 2018 ; Wen et al, 2019 ; Ye et al, 2019 ; Cisneros-Villanueva et al, 2021 ; Hou et al, 2021 ; Qian et al, 2021 ; Wu et al, 2021 ; Yang et al, 2021 ). HNSCC is certainly no exception, with its identification as a prognostic lncRNA signature using orthogonal partial least squares discriminant analysis (OPLS-DA) which integrates RNA-Seq data from TCGA database and matching clinical information from a large cohort of patients with HNSCC( Cao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…48 Knockdown of LINC00460 decreased the expression of FADS1 and increased miR-1224-5p regulating the cell proliferation and migration in OS. 49 Knockdown of LINC00460 suppressed NPC cell proliferation, migration, and invasion by targeting miR-30a-3p/Rap1A and miR-149-5p/IL6 50,51 ; LINC00460 promoted OC progression by binding miR-338-3p 52 ; LINC00460 prompted bladder urothelial carcinoma progression via sponging of miR-612 by elevating FOXK1 expression 53 ; LINC00460 accelerated pancreatic cancer by binding to the suppressor miR-491-5p 54 ; knockdown of LINC00460 suppressed proliferation cervical cancer cells by targeting miR-503-5p and miR-361-3p/Gli1 axis 55,56 such as PIK3/AKT, Wnt/β-catenin, etc. The most common mechanism of action of LINC00460 in various tumors is the specific absorption of miRNA as ceRNA.…”
Section: Discussionmentioning
confidence: 99%
“…For bladder urothelial carcinoma, Li et al 53 indicated that the high expression of LINC00460 was associated with poor survival, promoted cell proliferation and migration, and LINC00460 prompted tumor progression via miR‐612/FOXK1 axis. Moreover, LINC00460 accelerated PC by binding to miR‐491‐5p 54 . For cervical cancer, LINC00460 affected tumor progression by targeting miR‐503‐5p, 55 or by mediating the miR‐361‐3p/Gli1 axis 56 .…”
Section: Linc00460 In Various Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…The following supporting information can be downloaded at: , Table S1: List of ncRNAs that could be used as therapeutic targets or biomarkers for gastric cancer [ 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 ]; Table S2: List of ncRNAs that could be used as therapeutic targets or biomarkers for pancreatic cancer [ 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 ,…”
mentioning
confidence: 99%